(untitled) (International Journal of Physiotherapy, 2016)
Background: Endurance of the back muscles is important for stability of the trunk and therefore essential for normal functioning of an individual. Prone back extension exercises are traditional measures to improve back endurance. More recently Swiss ball exercises have become popular as a means to improve back endurance. Purpose of this study is to compare Prone back extension exercises with back extension exercise on Swiss ball on the improvement of the back extensor muscles performance, and thereby to find out which one is more appropriate for the prevention of back pain resulting from low extensor endurance. Back endurance can be measured by Bierring Sorensen endurance test. A low Sorensen score indicates low back endurance, which is associated with incidence of back pain. Methods: This study included 60 undergraduate students aged 18 to 23 years. The subjects were randomly divided into 2 equal groups. Pretest assessment was done by measurement of endurance of back extensors using Sorensen test. One group was given a series of prone back extension exercises on floor consisting of 5 levels. The second group was given a series of 5 exercises on Swiss ball. Each subject was assessed at the end of six weeks of intervention and after two weeks of finishing the regime (follow up) to compare the effectiveness of Prone back extension exercises with Swiss ball exercises. Results: The results indicated that both the groups showed improvement in Sorensen score after 6 weeks of exercise. The average improvements of Prone back extension exercises and Swiss ball groups were 60.83 seconds and 66 seconds respectively. At two weeks follow up there is a slight change in the Sorensen score, with an average reduction of 1.34% and 0.95% for Prone back extension exercises and Swiss ball group respectively. However comparison of improvements in Sorensen score of Prone back extension exercises with Swiss ball exercises showed there is no significant difference between the effectiveness of these two exercises programs (P = 0.26). Conclusion: There is no difference in the effects of Prone back extension exercises and Swiss ball exercises on the performance of back extensors and their endurance level were not significantly differing with the protocol used.